Shock characteristics evolution of detonation waves forward impacting on the solid wall - Ziwei Hou; Xiaolong Huang; Ning Li; Chunsheng Weng (AIP Advances, 2022)
The forward reflection of detonation waves on the solid wall will lead to a high pressure rise. The research systematically introduced the theoretical, numerical, and experimental exploration on the shock propagation characteristics of detonation waves forward impacting on a solid wall in the present work. The one-dimensional shock theory was carried out to solve the pressure rise ratio in this process. The exact solution and its variation law of a positive increase with filling pressure were expressed. One-dimensional simulations based on the space-time conservation element and solution element method were utilized to reveal the pressure decrease and velocity increase laws for the reflected shock wave. The blockage, oscillation, and attenuation phenomena of detonation waves and reflected shock waves under the effect of the tube–wall reflection were demonstrated in two-dimensional works. Experimental results from the detonation tube pressure test system showed a larger amplitude and duration of the reflected shock wave than the detonation wave. Pressure evolution and the formation of pressure plateaus were consistent with the simulation results. In addition, the time required for the pressure plateaus to decay to 0.5 times the Chapman-Jouget (C–J) detonation pressure is relatively constant under different filling conditions.